"Opt Out" and Access to Anesthesia Care for Elective and Urgent Surgeries among U.S. Medicare Beneficiaries. (March 2017) - Sun, Eric C.; Dexter, Franklin; Miller, Thomas R.; Baker, Laurence C.
Abstract : Background: In 2001, the Centers for Medicare and Medicaid Services issued a rule allowing U.S. states to "opt out" of the regulations requiring physician supervision of nurse anesthetists in an effort to increase access to anesthesia care. Whether "opt out" has successfully achieved this goal remains unknown. Methods: Using Medicare administrative claims data, we examined whether "opt out" reduced the distance traveled by patients, a common measure of access, for patients undergoing total knee arthroplasty, total hip arthroplasty, cataract surgery, colonoscopy/sigmoidoscopy, esophagogastroduodenoscopy, appendectomy, or hip fracture repair. In addition, we examined whether "opt out" was associated with an increase in the use of anesthesia care for cataract surgery, colonoscopy/sigmoidoscopy, or esophagogastroduodenoscopy. Our analysis used a difference-in-differences approach with a robust set of controls to minimize confounding. Results: "Opt out" did not reduce the percentage of patients who traveled outside of their home zip code except in the case of total hip arthroplasty (2.2% point reduction; P = 0.007). For patients travelling outside of their zip code, "opt out" had no significant effect on the distance traveled among any of the procedures we examined, with point estimates ranging from a 7.9-km decrease for appendectomy (95% CI, −19 to 3.4; P = 0.173) to a 1.6-km increase (95% CI, −5.1 to 8.2; P = 0.641) for total hip arthroplasty. There was also no significant effect on the use of anesthesia for esophagogastroduodenoscopy, appendectomy, or cataract surgery. Conclusions: "Opt out" was associated with little or no increased access to anesthesia care for several common procedures. Abstract : This investigation examined a different dimension of access to care and the influence of "opt out": the distance patients travel to obtain surgical procedures. For five common elective procedures and two common urgent procedures, "opt out" largely did not reduce the percentage of patients who traveled outside of their home zip code, and for patients who did travel outside of their zip code, "opt out" had no significant effect on the distance traveled. Results demonstrate that "opt out" was associated with little or no increased access to anesthesia care for several common procedures.Supplemental Digital Content is available in the text.